Current Debates in the Post-Soeharto Indonesian Islam: Examining the Intellectual Base of Liberal and Anti-liberal Islamic Movement - Muzakki, Akh. (Al-Jamiah Research Centre, 2007)
This article discusses intensively the current debate between those who support and against liberalism within pluralized Indonesian muslims. The two groups are represented by JIL (Jaringan Islam Liberal) and MD (Media Dakwah). The author compares three fundamental aspects of religious interpretations: epistemological assumptions, methodological framework, and subject-matter. Epistemological assumptions deal with philosophical foundations that are employed by JIL and MD as principles to understand Islam. Methodological framework means the way the two groups understand and interpret Islam and its teaching based on their philosophical foundations. In terms of subject-matter, the author discusses six issues, namely (1) ijtihad, (2) approaches to text, (3) the meaning of truth, (4) the minority and the oppressed, (5) freedom of religion, and (6) mundane and spiritual authority. From the three fundamental aspects of religious interpretations that are compared, the author concludes that JIL is a group of muslims who understand Islam by implementing liberalism, while MD represents a group of muslim who promote conservatism, purification, and anti-liberalism within Indonesian Islam.